2008
DOI: 10.24198/pjd.vol20no3.14119
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of physical and mechanical properties analysis of self made gypsum product with raw material from Tasikmalaya with standar ISO and factory made

Abstract: In early research, gypsum's product from Padalarang and Tasikmalaya had been compared and it is found that Tasikmalaya gypsum was better. In these research, it's used gypsum product from Tasikmalaya with wet calcination method using autoclave. This research consisted of four samples divided into three control groups and one treatment group. Research's sample consisted of 45 units and 15 units data from the last research. To compared physical and mechanical properties, every samples was tested in three treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Other research on local gypsum products showed that the average setting time of the self-made gypsums was around 8 minutes and 7 seconds and 3 minutes and 40 seconds. 14 The study above also reported an average setting time of 20 minutes and 21 seconds for dental plaster and 10 minutes and 34 seconds for dental stone. 14 …”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Other research on local gypsum products showed that the average setting time of the self-made gypsums was around 8 minutes and 7 seconds and 3 minutes and 40 seconds. 14 The study above also reported an average setting time of 20 minutes and 21 seconds for dental plaster and 10 minutes and 34 seconds for dental stone. 14 …”
Section: Discussionmentioning
confidence: 84%
“… 14 The study above also reported an average setting time of 20 minutes and 21 seconds for dental plaster and 10 minutes and 34 seconds for dental stone. 14 …”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation